The effects of a goal setting program on the exercise commitment and fitness levels of university students - Buckman, Rahmin (Western Washington University, 2011)
The purpose of the current study was to examine the effects a goal setting program had on exercise commitment and aerobic fitness among university students. Obesity and a lack of sufficient physical activity continue to be a problematic and increasing epidemic in the United States. Some theorists have utilized goal setting as an intervention to increase commitment effectiveness of exercise participants. In the current study, a two-way between-within experimental design was utilized involving two separate physical education activity classes (beginning jogging) at Western Washington University. One of the classes (experimental group) underwent a goal setting program consisting of educational, constructive, and evaluative components aimed to pursue a self-selected aerobic fitness goal while the other class (control group) did not. Components of exercise commitment and aerobic fitness level measurements were taken at the onset and again at the termination of the goal setting implementation. Upon computing 11 separate two-way between-within ANOVAs and effect sizes, the results produced little statistical significances and effects. However, the results of this study revealed several practical trends related to exercise commitment and physical activity. Findings and considerations for future direction are provided in hopes that further research and practical methods regarding goal setting, exercise commitment, and fitness level can be improved upon.